Analisis Nilai Tambah Ayam Pedaging Menjadi Bakso Ayam Di Kecamatan Belitang Kabupaten Oku Timur - Parmaji (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2019)
The objectives of this study were to: 1) determine the added value of broilers into meatballs in Belitang District, East OKU Regency, 2) to determine the financial feasibility of making chicken meatballs in Belitang District, East OKU Regency. The results showed that the total production cost for the business of making chicken meatballs in Belitang District, East OKU Regency in one production process on average is Rp. 358,520, revenue is Rp. 440,000, and the income received is Rp. 81,480. The amount of added value in the business of making chicken meatballs in Belitang District, East OKU Regency in one process is IDR 162,813 or 45,562 / Kg. This shows that each making chicken meatball from 1 kg of chicken will provide an added value of Rp. 44,284. The business of making chicken meatballs in Belitang District, East OKU Regency is financially feasible, this can be seen from the calculation of the NPV value of IDR 27,692,459, the IRR value is 64.99% and the Net B / C value is 1.98. .